A Sam68‐dependent alternative splicing program shapes postsynaptic protein complexes. (29th January 2019) - Witte, Harald; Schreiner, Dietmar; Scheiffele, Peter
Abstract: Alternative splicing is one of the key mechanisms to increase the diversity of cellular transcriptomes, thereby expanding the coding capacity of the genome. This diversity is of particular importance in the nervous system with its elaborated cellular networks. Sam68, a member of the Signal Transduction Associated RNA‐binding (STAR) family of RNA‐binding proteins, is expressed in the developing and mature nervous system but its neuronal functions are poorly understood. Here, we perform genome‐wide mapping of the Sam68‐dependent alternative splicing program in mice. We find that Sam68 is required for the regulation of a set of alternative splicing events in pre‐mRNAs encoding several postsynaptic scaffolding molecules that are central to the function of GABAergic and glutamatergic synapses. These components include Collybistin ( Arhgef9 ), Gephyrin ( Gphn ), and Densin‐180 ( Lrrc7 ). Sam68‐regulated Lrrc7 variants engage in differential protein interactions with signalling proteins, thus, highlighting a contribution of the Sam68 splicing program to shaping synaptic complexes. These findings suggest an important role for Sam68‐dependent alternative splicing in the regulation of synapses in the central nervous system. Abstract : This study examines at a genome‐wide level the alterations in alternative splicing in the hippocampus of knock‐out mice for the RNA‐binding protein Sam68. Sam68 preferentially regulates transcript isoforms of genes encoding synaptic proteins, including the glutamatergic scaffolding protein densin‐180/Lrrc7. Sam68‐dependent splice isoforms differ in coupling to postsynaptic signaling components, suggesting a potential mechanism for the regulation of synaptic plasticity.